KAJIAN TEKNIS PENINGKATAN PEROLEHAN CASSITERITE DENGAN MENGGUNAKAN PAN AMERICAN JIG CLEAN UP PADA UNIT KONSENTRASI TAMBANG BESAR OPEN PIT TB. 1.42 PEMALI PT. TIMAH (PERSERO), TBK - Riri Ferdian; Bambang Heriyadi; Rijal Abdullah (Journals Mining Engineering : Bina Tambang, 2014)
ABSTRACT The concentration units at Open Pit TB 1.42 Pemali is using Pan American Jig as its main equipment. There are two steps applied to the Pan American Jig; primary jig and clean up jig. At the clean up jig operational step, the final gain of cassiterite should get a serious attention. To obtain the cassiterite concentrate content as conditioned by Tin Ore Processing Center (PBBT) Pemali, that is 40% - 65% with 97% gain, there should be an analysis to the jig operation variables that are being used and analysis to the resulting product, so that a good suitability would be acquired in order to increase the cassiterite gain based on the operational standard in every clean up jig step. According to the sampling and the calculation of the final gain of cassiterite at clean up jig, the value of the right clean up jig is 96.82%, whereas the value of the left clean up jig is lower, 91.43%. The final concrete content were resulted as follow: the right clean up jig, compartment A 38.31% SnO2, compartment B 20.76% SnO2., compartment C 13.80% SnO2.Whereas,the left clean up jig, compartment A 49. 15% SnO2,compartment B 25.09% SnO2, compartment C 23. 43% SnO2. In order to increase the cassiterite gaining through clean up jig based on the requirement, that is 97%, which done by: first, change the setting of the compartment A, B and C hit length in a chronological order, 18mm, 10mm, and 6mm with push speed resulted at the three compartments 5.943cm/s, 3.302 cm/s, and 1.981 cm/s. Second, the management of horizontal crossflow with the characteristics and the jig feed rate. Third, the uniformity of bed jig shape and size, the placement of bed jig size should be adapted with the sequence of compartment and the jig steps. Fourth, arrange the entering feed pulp by installing feed combs grader flow at feed box.Key words: jig, pan american jig, cassiterite